2020
DOI: 10.3126/jcmsn.v16i3.31299
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile and Outcomes in Patients with Acute Pancreatitis attending a Teaching Hospital at Gandaki Province, Nepal

Abstract: Background: Acute pancreatitis (AP) is inflammatory process of pancreas presenting with acute abdominal pain.The majority of patients have mild disease. Some patients develop local and systemic complications with increased morbidity and mortality. This study was undertaken to describe the clinical profile and outcomes in patients with acute pancreatitis.   Methods:  A cross-sectional hospital based study comprising of 62 consecutive patients with acute pancreatitis were enrolled between Jan 2019 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
3
2
0
Order By: Relevance
“…More than 3 folds raised amylase and/or lipases were seen in 82.7 of patients. Similar to this study, more than 3 folds rise in amylase/lipase was seen in 87.1%, 81% and 82% in study by Bhattrai et al, 8 Reid et al 13 and Rao et al 14…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…More than 3 folds raised amylase and/or lipases were seen in 82.7 of patients. Similar to this study, more than 3 folds rise in amylase/lipase was seen in 87.1%, 81% and 82% in study by Bhattrai et al, 8 Reid et al 13 and Rao et al 14…”
Section: Discussionsupporting
confidence: 89%
“…The most common presentation in our study was abdominal pain (97%) followed by vomiting (66.7%) and fever (17.3%). Pain abdomen (100%) followed by vomiting (42.27%) by Negi et al, 10 abdominal pain (100%) followed by nausea (83.9%), vomiting (66.1%)by Bhattrai et al 8 and abdominal pain (79%), vomiting (71.4%) and fever (23.8%) by Reid et al 13 all studies on acute pancreatitis showed presenting symptoms similar to our study. More than 3 folds raised amylase and/or lipases were seen in 82.7 of patients.…”
Section: Discussionsupporting
confidence: 86%
“…In our study 85% of the patients with acute pancreatitis presented with nausea and vomiting. Similarly, 83.9% 24 and 90% of patients presented with nausea and vomiting respectively in other studies. 25 Our study showed the three-fold rise in serum amylase and serum lipase to be present in 50% and 36.67% of the patients admitted with acute pancreatitis respectively.…”
Section: Discussionsupporting
confidence: 77%
“…27 Likewise, our study showed leukocytosis (TLC>11,000/ mm 3 ) in 23.33% of the patients with acute pancreatitis, Free Full Text Articles are Available at www.jnma.com.np which is lower than the findings from the studies which showed leukocytosis in two-thirds of the patients. 24,26 Previous studies have reported decreased serum calcium among 8.6% 25 and 18% 26 of the patients with acute pancreatitis. The findings from these studies were similar to our study where 8.3% of the patients having acute pancreatitis presented with hypocalcemia (<8.5 mEq/L).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation